2015
DOI: 10.1523/jneurosci.2302-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Rapid Local RhoA Synthesis Is Required for Hippocampal Synaptic Plasticity

Abstract: Dendritic protein synthesis and actin cytoskeleton reorganization are important events required for the consolidation of hippocampal LTP and memory. However, the temporal and spatial relationships between these two processes remain unclear. Here, we report that treatment of adult rat hippocampal slices with BDNF or with tetraethylammonium (TEA), which induces a chemical form of LTP, produces a rapid and transient increase in RhoA protein levels. Changes in RhoA were restricted to dendritic spines of CA3 and CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 61 publications
1
42
0
Order By: Relevance
“…Many previous publications showed similar examples in which either loss (Shmerling et al, 1998) or dysfunction (Chen et al, 1999; Hashimoto et al, 1999) of cerebellar granule cells leads to impaired PF-PC transmission and ataxia. In addition, we and another lab previously found that dysregulation of calpain or Akt affects actin polymerization, which is important for synapse formation and function and regulating the shape of the dendritic spines (Briz et al, 2015; Huang et al, 2013). We previously reported that calpain-1 activation was critical for induction of LTP at hippocampal synapses (Wang et al, 2014), and it has been repeatedly proposed that establishment of synaptic contacts during the postnatal period might require a mechanism similar to LTP (Chaudhury et al, 2015).…”
Section: Discussionmentioning
confidence: 83%
“…Many previous publications showed similar examples in which either loss (Shmerling et al, 1998) or dysfunction (Chen et al, 1999; Hashimoto et al, 1999) of cerebellar granule cells leads to impaired PF-PC transmission and ataxia. In addition, we and another lab previously found that dysregulation of calpain or Akt affects actin polymerization, which is important for synapse formation and function and regulating the shape of the dendritic spines (Briz et al, 2015; Huang et al, 2013). We previously reported that calpain-1 activation was critical for induction of LTP at hippocampal synapses (Wang et al, 2014), and it has been repeatedly proposed that establishment of synaptic contacts during the postnatal period might require a mechanism similar to LTP (Chaudhury et al, 2015).…”
Section: Discussionmentioning
confidence: 83%
“…Actin polymerization was quantified by measurement of “rhodamine-phalloidin fluorescent enhancement”, as previously described with minor modifications [29]. For details, see Supplementary materials and methods.…”
Section: Methodsmentioning
confidence: 99%
“…Rapamycin treatment results in reduced latephase LTP induced by high-frequency stimulation in the hippocampus; the early phase of LTP is unaffected 5 . Moreover, rapamycin has been shown to block the synaptic potentiation induced by brain-derived neuro trophic factor in hippocampal slices 27 . By contrast, exposure of mouse hippocampal slices to the metabotropic glutamate receptor (mGluR) agonist (RS)-3,5-dihydroxyphenylglycine (DHPG) increased phosphorylation of AKT and mTOR in CA1 and increased mGluR-dependent LTD 28 , and rapamycin prevented DHPG-induced mGluR-mediated LTD 28 .…”
Section: Malformations Of Cortical Development (Mcds)mentioning
confidence: 99%